KASHKATASH GLACIER FLUCTUATIONS IN THE XVII–XXI CENTURIES FROM CARTOGRAPHIC, DENDROCHRONOLOGICAL AND LICHENOMETRIC DATA - I. S. Bushueva; O. N. Solomina (Лëд и снег)
We focused our study on the retreat of a typical valley glacier Kashkatash, located in the Elbrus Area. We compared the old photographs of the glacier forefields (H. Burmester, 1911; H. Altberg, 1927; E.N. Lukasheva, 1932; unknown author, 1939) with the aerial photograph of 1957, 1965, 1987, maps of scale 1:100 000 (1890) and 1:25 000 (1950s), satellite images (CORONA of 1971, ASTER of 2005, EROS of 2006), oblique photographs taken in 1980s–2000s and plans, created by different researches. Using cartographic material and old photographs we reconstructed 14 positions of glacier tongue over the last 120 years. We estimated the linear glacier retreat and the age of numerous stadial moraines basing on geomorphic, tree-ring and lichenometric data and correlated our results with previous sparse glacier fluctuation reconstructions in this region. We identified at least 13 end moraines within the distance of 900 meters from the up-to-date glacier front position. The minimum age of the outer moraine is 450 years according to the tree-ring data. One tree growing on this moraine was damaged by a boulder falling down from a younger moraine under formation in the period from autumn 1839 to spring 1840. Three moraines were deposited in 1870s–1890s. In 20th century the glacier advanced in 1910-s, 1920-s, and 1970–1980-s.